Unions And Economic Performance In Developing Countries: Case Studies From Latin America (2017)
This paper analyzes the economic impact of unions on productivity in the manufacturing sector across six Latin American countries: Argentina, Bolivia, Chile, Mexico, Uruguay, and Panama. Using an augmented Cobb-Douglas production function, the paper finds that unions have positive, but mostly small, effects on productivity, with the exception of Argentina, with a large negative effect, and Bolivia, with no effect. An analysis on profitability shows that, in most cases, the positive productivity effects barely offset higher union compensation, and that unions are negatively related to investment in capital and R & D. Different explanations for these effects are discussed.